The incidence of obesity in patients seeking treatment at Ibnu Sina Hospital: Indonesia - Makmun, Armanto; Karim, Marzelina; Bamahry, Aryanti; Vitayani, Sri; Purnama, Indah Dian (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2023)
Obesity is a condition of excess nutrition or being overweight that can interfere with health. Obesity is a multifactorial disease caused by several risk factors such as gender, genetic factors, food intake, physical activity, and socioeconomic, many diseases can be caused by obesity, such as type 2 diabetes mellitus, cardiovascular disease, and various other diseases, so that researchers are interested to conduct research related to the characteristics of the disease in obesity conditions treated at the Ibnu Sina Hospital Makassar in 2019. This study used a descriptive design with a cross-sectional using secondary data taken from the Ibnu Sina Hospital Makassar. Most patients are in the age range of 20- 60 years with a total of 32 people (71.1%), female sex with a total of 30 people (66.6%), Obesity Body Mass Index I with a total of 39 people (86.6%). , work as a housewife with a total of 18 people (40%), high school education level with a total of 17 people (37.7%), and type of diabetes mellitus type 2 with a total of 20 people (44.4%).